RISK FACTORS FOR THE DEVELOPMENT OF RECURRENCES OF OBSTRUCTIVE BRONCHITIS IN CHILDREN - Zhamshedova Sozhida Zhamshedovna; Ibragimova Marina Fedorovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Introduction. Recently, the development of a new field of medicine, riskology, the study of risk factors for disease development, has become increasingly important. Research papers have described risk factors for acute obstructive bronchitis in children, including a complicated premorbid background: perinatal pathology, a history of allergies, malnutrition, early artificial feeding, and respiratory diseases experienced at the age of 6-12 months. Genealogical risk factors for recurrent obstructive bronchitis in children, depending on the degree of kinship of the proband, remain poorly understood. Studying these factors is crucial for identifying risk groups for recurrent obstructive bronchitis in children and improving preventive measures and clinical monitoring.